IMPLEMENTATION ANALYSIS OF OCCUPATIONAL SAFETY AND HEALTH IN THE OPERATING PROCESS A CRUSHER MACHINE AT THE PLASTIC WORKSHOP OF POLYTECHNIC ATK YOGYAKARTA - Muhammad Ikhwan (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2023)
The Plastic Laboratory is one of the Laboratories of the Rubber and Plastic Processing Technology Study Program located at the Polytechnic ATK Yogyakarta. Plastic Workshop has several machines including Injection Molding machine, Blow Molding machine, Crusher machine and Mixer machine. In the operation of the crusher machine, there is a danger of microplastics produced as a by-product of the plastic enumeration process where the raw material is in the form of a practicum reject product on the Injection Molding and Blow Molding machines. Microplastics are types of plastic waste that are smaller than 5 mm in size and are grouped into 2 types, namely primary and secondary microplastics. The transfer of microplastics from the environment into the human body can occur both primary (directly from the environment into the human body in inorganic form) and secondaryly (entering through the food chain, by consuming organisms polluted with microplastics). Primary transfer can occur through the digestive (digesti) and respiratory (inhalation) systems. Microplastics can enter the human body primarily through inhalation, because microplastics can float in the air. From the hierarchy of hazard control, Administrative Control and the application of Personal Protective Equipment is the hierarchy that best suits the conditions and needs in the plastic laboratory. Where with Administrative Control, which ensures that all people in the laboratory and practice who operate crusher machines are required to use Personal Protective Equipment, the impact of microplastic hazards can be minimized properly. Another thing to note is that the provision of engineering gloves, respirator masks and earmuffs should be done periodically and in sufficient quantities.